The inverse function of the given function y = x² + 4 will be y = √(x - 4).
<h3>What is the inverse function?</h3>
Let the function f is given as
y = m(x + a) + c
Then the inverse function of the function f will be given by swapping x with y and y with x.
The definition of simplicity is making something simpler to achieve or grasp while also making it a little less difficult.
The function is given below.
y = x² + 4
The inverse function of the function y = x² + 4 is given as,
Replace x with y and y with x, then we have
x = y² + 4
Solve the equation for y, then the equation is rewritten as,
x = y² + 4
y² = x - 4
y = √(x - 4)
The inverse function of the given function y = x² + 4 will be y = √(x - 4).
More about the inverse function is given below.
brainly.com/question/2541698
#SPJ12
what is the question. I am kinda confused what you want me to solve. Please state the question more clearly.
-brainly.com
Answer:
I think 15
Step-by-step explanation:
15+15=30, so both 3 or 4 point questions have 15 problems each, hope this helped
6x + 2 - 2 = 14 - 2
6x/6 = 12/6
x = 2